Optimizing Supply Chain Networks for Quality Compliance: A Comprehensive Analysis - Maneesh Karumathil Nair, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the critical challenges and opportunities in optimizing supply chain networks for quality compliance in today's globalized business environment. It explores how organizations navigate complex quality management requirements across diverse geographical locations while integrating advanced technologies for enhanced performance. The article investigates multi-criteria decision frameworks, predictive analytics, IoT-enabled monitoring, and blockchain-based traceability solutions through comprehensive case studies in the pharmaceutical and food & beverage industries. Through the evaluation of implementation strategies and risk mitigation approaches, the study provides insights into successful quality management system deployment and offers practical recommendations for organizations seeking to enhance their supply chain quality capabilities.
Keywords: Supply Chain Quality Management; Risk Mitigation Strategies; Quality Compliance Optimization; Technology Integration; Implementation Framework